2007
DOI: 10.1042/bst0350211
|View full text |Cite
|
Sign up to set email alerts
|

Role of class II phosphoinositide 3-kinase in cell signalling

Abstract: Although it is now well established that PI3K (phosphoinositide 3-kinase) is a key enzyme in several intracellular processes, there are still relatively few reports that precisely identify the specific isoforms of PI3K actually involved in such events. The lack of specific inhibitors has made it particularly difficult to address the physiological roles of some isoforms, such as the members of class II. As a consequence, there is still relatively little understanding of the role of these enzymes and the questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 43 publications
3
74
0
Order By: Relevance
“…Notably, in vitro studies demonstrated that PtdIns is the preferred target of class II PI3K, although this kinase also displays activity toward PtdIns4P. 161 It is therefore plausible that class II PI3K is a contributor to the PtdIns3P pool in addition to class III PtdIns3K. In support of this hypothesis, there is emerging evidence that class II PI3K is a significant producer of PtdIns3P, and class II PI3K holds a wide spectrum of functions ranging from cell signaling, to cell migration and vesicle trafficking.…”
Section: Regulation Of Autophagy By Pik3c3 Via Other Interacting Partmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, in vitro studies demonstrated that PtdIns is the preferred target of class II PI3K, although this kinase also displays activity toward PtdIns4P. 161 It is therefore plausible that class II PI3K is a contributor to the PtdIns3P pool in addition to class III PtdIns3K. In support of this hypothesis, there is emerging evidence that class II PI3K is a significant producer of PtdIns3P, and class II PI3K holds a wide spectrum of functions ranging from cell signaling, to cell migration and vesicle trafficking.…”
Section: Regulation Of Autophagy By Pik3c3 Via Other Interacting Partmentioning
confidence: 99%
“…In support of this hypothesis, there is emerging evidence that class II PI3K is a significant producer of PtdIns3P, and class II PI3K holds a wide spectrum of functions ranging from cell signaling, to cell migration and vesicle trafficking. [161][162][163][164][165][166] One hint implying a role of class II PI3K in autophagy was provided by the studies on cell corpse clearance by phagocytosis in C. elegans. 167,168 In this process, autophagy is required for phagosome maturation and clearance of apoptotic cells; most importantly, class II PI3K was identified as a complementary kinase producing PtdIns3P on phagosomes, indispensable for the degradation of cell corpses in C. elegans.…”
Section: Regulation Of Autophagy By Pik3c3 Via Other Interacting Partmentioning
confidence: 99%
See 1 more Smart Citation
“…The active site lysine (Lys802 in p110α and Lys833 in p110γ) is critical for catalysis and is highly conserved in lipid and protein kinases. Wortmannin also targets class II PI3K C2β (IC 50 =1.6 nM), the human class III PI3K hVps34p (IC 50 = 2.5 nM), type III PI4Ks (IC 50 =50-300 nM) and polo-like protein kinases that regulate mitosis (IC 50 =24-48 nM) [60][61][62][63][64]. Not surprisingly, considering the similarity between the PI3K and PIKK catalytic domains, wortmannin also irreversibly inhibits PIKK family members.…”
Section: Mtor Kinase Inhibitorsmentioning
confidence: 99%
“…In addition, use of immobilized LY294002 showed that the drug binds tightly to numerous non-kinase proteins with diverse functions, with as yet unknown biological consequences [80]. Class II PI3Ks (IC 50 =6.9-19 μM) and PI4Ks are relatively resistant to LY294002 as compared with the class I enzymes [60,61]. By contrast, the PIKK family members SMG-1, DNA-PK, and mTOR are targeted at low micromolar concentrations that also inhibit class I PI3Ks [41,65,82,83].…”
Section: Mtor Kinase Inhibitorsmentioning
confidence: 99%